Evolving Towards the Internetworked Enterprise Technological and Organizational Perspectives - Passiante, Giuseppina; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
A new model of business has emerged within the Digital-Economy called Internetworked Enterprise (IE); it$1 (Bs a model that posits networks, communities of individuals and refusal of a centralized mindset as the core elements of the new frame of reference. Internetworked Enterprises are called by some scholars 'Extended' Enterprises, which use digital network to co-operate and compete with other e-business community partners by exchanging knowledge and information across trans-national borders. Evolving Towards the Internetworked Enterprise: Technological and Organizational Perspectives is an edited volume based on a three year research project financed by the Italian Ministry of Research and Education. Researchers for this project are located at Polytechnic of Milan, University of Milan, University of Chieti, Engineering S.P.A and ISUFI-University of Salento. This book presents an overview of IE business methodologies, models, and an interpretative framework analyzing the sector and organizational contingencies that influence the digitalization of organizational processes in networks of SMEs (Small and Medium Enterprise). A set of case studies that provide empirical evidence on the IE phenomenon is included as well. This book is designed for advanced-level students in computer science and business management concentrating on e-business, digital computing, information technology, economics of technology and innovation management as a reference or secondary text book. Practitioners working in these fields as corporate strategic planners and consultants will also find this book a valuable asset.s
Towards an Internetworked Enterprise: some issues to be discussed -- A methodology aimed at fostering and sustaining the development processes of an IE-based industry -- A network-oriented business modeling environment -- Model-based service-oriented architectures for Internetworked Enterprises -- A technological infrastructure to sustain Internetworked Enterprises -- Monitoring Business Processes -- SuperJet International case study: a business network start-up in the aeronautics industry -- Avio case study: the MRO process -- Inter-organizational design: exploring the relationship between formal architecture and ICT investments -- Communication flows in an SME network: the C.I.S.I consortium case -- Tisettanta case study: the interoperation of furniture production companies -- An analysis of models and practices in Human Resource Management processes and the relationship between firms and outsourcers: a case study.
Keywords: Computer science; Computer Communication Networks; Information systems; Electronic data processing; Information Systems; Computer Science; e-Commerce/e-business.; Information Systems Applications (incl.Internet).; Management of Computing and Information Systems; Computing Methodologies; Computer Communication Networks